Laparoscopy versus laparotomy for the management of penetrating abdominal trauma: A systematic review and meta-analysis. (October 2016) - Hajibandeh, Shahin; Hajibandeh, Shahab; Gumber, Ashutosh O.; Wong, Chee Siong
Abstract: Background: Controversy exists regarding the role of laparoscopy in the evaluation of patients with penetrating abdominal trauma (PAT). Our objective was to perform a comprehensive review of the literature and conduct a meta-analysis to compare outcomes of laparoscopy and laparotomy in PAT. Methods: In accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement standards, we conducted a systematic search of electronic information sources, including MEDLINE; EMBASE; CINAHL; the Cochrane Central Register of Controlled Trials (CENTRAL); the World Health Organization International Clinical Trials Registry; ClinicalTrials.gov; ISRCTN Register, and bibliographic reference lists. We applied a combination of free text and controlled vocabulary search adapted to thesaurus headings, search operators and limits in each of the above databases. Missed injury, mortality, and complications were defined as the primary outcome parameters. Procedure time, length of hospital stay, sensitivity and specificity of the procedure were the secondary outcomes. Combined overall effect sizes were calculated using fixed-effect or random-effects models. Results: We identified one randomised controlled trial (RCT) and 8 observational studies comparing outcomes of laparoscopy with laparotomy in PAT. Laparoscopy was associated with a significantly lower risk of wound infection (Odd ratio (OR): 0.55; 95% Confidence interval (CI), 0.37–0.81, P = 0.003) and pneumonia (OR: 0.22; 95% CI, 0.13–0.37, P < 0.00001), and a significantly shorter length of hospital stay (Mean difference (MD): −3.05; 95% CI, −4.68 to −1.42, P = 0.0002) and procedure time (MD: −27.99; 95% CI, −43.17 to −12.80, P = 0.0003) compared with laparotomy. Laparoscopy was 100% sensitive in most of the included studies and avoided non-therapeutic laparotomies in 45.6% of patients. Conclusions: Our analysis of best available evidence mainly from heterogeneous observational studies has demonstrated that laparoscopic evaluation of haemodynamically stable patients with PAT may be safe and can reduce post-operative complications and length of hospital stay. The most important advantage of laparoscopy is avoidance of non-therapeutic laparotomies which are associated with considerable morbidity. However, no definitive conclusion can be made regarding the therapeutic role of laparoscopy in PAT based on the available evidence and future research is indeed required. Highlights: Laparoscopic evaluation of haemodynamically stable patients with PAT is safe and can reduce post-operative complications. It is associated with a very low missed injury rate as reflected by its high sensitivity. The most important advantage of laparoscopy is avoidance of non-therapeutic laparotomies. The best available evidence comes mainly from heterogeneous observational studies. High level evidence from well-designed RCTs are indeed required to facilitate more reliable meta-analysis.